WACANA PENDIDIKAN ISLAM MULTIKULTURAL UNTUK KEHARMONISAN HIDUP BERBANGSA - Dalmeri, Dalmeri (Sekolah Pascasarjana UGM, 2015)
Indonesiaâs diversity of ethnic, culture, tradition, and religion have aroused the dynamics of culturaldiversity and positive civilization. If it is not managed wisely and comprehensively, it will cause conflictand disintegration. Multicultural education in Indonesia should not only become an academic discourse,but it also needs to be implemented in the concrete sphere in the educational realm. A conceptual framefor its implementation is neded, that is why, the problems caused by the effects of the diversity andreligious bias do not become a heavy burden for the country. As for the students, this paper explainsmulticultural education in Islamic education and process to cultivate values of beliefs and importanceof unique recognition for every ethnic, culture, and other social groups.